The Gothenburg MCI study: Design and distribution of Alzheimer's disease and subcortical vascular disease diagnoses from baseline to 6-year follow-up. Issue 1 (January 2016) - Wallin, Anders; Nordlund, Arto; Jonsson, Michael; Lind, Karin; Edman, Åke; Göthlin, Mattias; Stålhammar, Jacob; Eckerström, Marie; Kern, Silke; Börjesson-Hanson, Anne; Carlsson, Mårten; Olsson, Erik; et al.
There is a need for increased nosological knowledge to enable rational trials in Alzheimer's disease (AD) and related disorders. The ongoing Gothenburg mild cognitive impairment (MCI) study is an attempt to conduct longitudinal in-depth phenotyping of patients with different forms and degrees of cognitive impairment using neuropsychological, neuroimaging, and neurochemical tools. Particular attention is paid to the interplay between AD and subcortical vascular disease, the latter representing a disease entity that may cause or contribute to cognitive impairment with an effect size that may be comparable to AD. Of 664 patients enrolled between 1999 and 2013, 195 were diagnosed with subjective cognitive impairment (SCI), 274 with mild cognitive impairment (MCI), and 195 with dementia, at baseline. Of the 195 (29%) patients with dementia at baseline, 81 (42%) had AD, 27 (14%) SVD, 41 (21%) mixed type dementia (=AD + SVD = MixD), and 46 (23%) other etiologies. After 6 years, 292 SCI/MCI patients were eligible for follow-up. Of these 292, 69 (24%) had converted to dementia (29 (42%) AD, 16 (23%) SVD, 15 (22%) MixD, 9 (13%) other etiologies). The study has shown that it is possible to identify not only AD but also incipient and manifest MixD/SVD in a memory clinic setting. These conditions should be taken into account in clinical trials.